Academic Senate Minutes 2019-09-12 - Academic Senate:::::::::
Agenda Approved. Minutes of 8/23/18 Approved. Chair Report. President Report. Provost Report. VP of A&F Report. VP of Student Affairs Report. APARC Report. EPC Report. Faculty Eligible for Emeritus status approved for the Senate's consent calendar. Appoint Ex Com member to SEC – no volunteer. Charge APARC/ATISS with Stevenson Remodel – referred to both APARC and ATISS to send chair or designee. Refer module discussion to APARC – Approved. Senate agenda approved. Graduate Studies Subcommittee reports received. FASC Report. SAC Report.